COMPARATIVE EVALUATION OF TOXICITY OF ELSAN IN CONTINUOUS FLOW AND STATIC SYSTEMS WITH REFERENCE TO OXYGEN CONSUMPTION AND EXCRETION IN OPHIOCEPHALUS PUNCTATUS (BLOCH) - Rao, K R S Sambasiva; Rao, K Siva Prasada; Sahib, I Kabeer Ahmed; Rao, K V Ramana (Indian Journal of Fisheries, 2011)
COMPARATIVE EVALUATION OF TOXICITY OF ELSAN IN CONTINUOUS FLOW AND STATIC SYSTEMS WITH REFERENCE TO OXYGEN CONSUMPTION AND EXCRETION IN OPHIOCEPHALUS PUNCTATUS (BLOCH)